Impact Measures of the Article Headlines-Factual Proposition in the Delfi.lt Portal - Liepinytė-Kytrienė, Diana (Taikomoji kalbotyra, 2013)
The object of the article is article headlines of the internet news portal Delfi.lt: factual statements containing the mentioning of a person by their name, surname or pseudonym. A headline is perceived as a complex representative unit, where a complex means, namely, employing accompanying notes and illustrations, and is used to achieve its main functions: to inform and affect. The aim of the article is to identify the effect of factual statements employed in headlines, which the statements have on the person mentioned and how they serve in drawing the readers’ attention. The material for the analysis was collected from the internet news portal Delfi.lt. A total of 191 headlines including the illustrations were looked into. The analysis comprised not only the evaluation of the headlines but also the articles in their entirety, including illustrations and commentaries. The qualitative analysis of headlines as factual statements was carried out in three aspects: description of a person, naming the action performed by the person, and the relationship of the person and the illustration. The research revealed that the headlines of the internet news portal Delfi.lt often employ a person as a means of drawing the readers’ attention as well as illustrations as a means of conveying visual information complementing the headlines. It turned out that in the headlines taking the form of a factual statement, the readers’ attention is mostly drawn by the information of negative nature where the accompanying expressive illustrations present well- known persons, mainly Lithuanian politicians, businessmen, and sportsmen. Descriptions of a person exert no influence on the popularity of the article in cases where people well known to society are referred to but are of particular importance when dealing with much less known people. Expressions in the past simple tense are attractive to the readers since the expressions provide a possibility, based on the facts presented, to design potential consequences on one’s own. Expressive headlines with accompanying expressive illustrations, where the presented scene does not only specify the idea of the headline but also complements it with intriguing meanings, enjoy the highest popularity. Therefore, headlines and illustrations kindle the readers’ emotions and encourage them to interpret their own meanings.
Keywords: internet news portal; headline; impact measures; personal naming; factual proposition; stylistics